Mussel-inspired grafting pH-responsive brushes onto halloysite nanotubes for controlled release of doxorubicin. (5th November 2022) - Hemmatpour, Hamoon; Haddadi-Asl, Vahid; Khanipour, Fatemeh; Stuart, Marc C.A.; Lu, Liqiang; Pei, Yutao; Roghani-Mamaqani, Hossein; Rudolf, Petra
Graphical abstract: Highlights: Halloysite nanotubes functionalized with polydopamine present the proper functional groups for the grafting of alky bromide moieties. Using atom transfer radical polymerization poly(N, N-dimethylaminoethyl methacrylate) chains can be grown on the nanotube surface decorated with alkyl bromide groups. Grafting of poly(N, N-dimethylaminoethyl methacrylate) chains on halloysite nanotubes leads to a twice higher loading capacity for doxorubicin. The coiled chain conformation of poly(N, N-dimethylaminoethyl methacrylate) chains in media with the physiological pH value of 7.4 suppresses the release of doxorubicin molecules. The stretched chain conformation combined with the repulsion between the doxorubicin molecules and protonated poly(N, N-dimethylaminoethyl methacrylate) chains accelerates the release of doxorubicin molecules in an acidic medium. Abstract: The development of stimuli-responsive drug nanocarriers is an increasingly important area in nanomedicine because efficient delivery of toxic drugs to targeted tissues minimizes side effects. The specific objective of this study was to synthesize and characterize a novel pH-responsive drug carrier based on halloysite nanotubes for the controlled release of the anticancer drug doxorubicin. Poly(N, N-dimethylaminoethyl methacrylate) brushes were grafted from the surface of halloysite nanotubes using the combination of mussel-inspired polydopamine surface modification and activators regenerated by electron transfer in atom transfer radical polymerization. The chemical structure and morphology of the modified halloysite nanotubes were investigated by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, thermal gravimetric analysis as well as scanning and transmission electron microscopies. Dynamic light scattering and zeta potential analysis were carried out to evaluate the pH-responsivity of the functionalized halloysite nanotubes. The results of the drug loading and release study of pristine and functionalized halloysite nanotubes showed that grafting of poly(N, N-dimethylaminoethyl methacrylate) brushes on the polydopamine-modified halloysite nanotubes surface leads to a drastic increase in doxorubicin loading capacity and a highly pH-sensitive release behaviour. Less than 10 % of the loaded doxorubicin was released from poly (N, N-dimethylaminoethyl methacrylate)-grafted halloysite nanotubes at pH 7.4 after 24 h; in contrast, at pH 5.5 there was a continuous release of doxorubicin totalling 13 % in the first 30 min, i.e. lower than for the pristine halloysite nanotubes (32 %), but reaching 48 % after 24 h. Poly (N, N-dimethylaminoethyl methacrylate)-grafted halloysite nanotubes can hence be considered as a potential candidate for delivering highly toxic drug molecules to the acidic target sites.